ENHANCED IMMUNIZATION COVERAGE THROUGH INTERVENTIONS FOR CHILDHOOD CLUSTER DISEASES IN DEVELOPING COUNTRIES - Mureed, Sheh; Somronghtong, Ratana; Kumar, Ramesh; Ghaffar, Abdul; Chapman, Robert S (Journal of Ayub Medical College Abbottabad, 2015)
Background: Globally immunisation has to be considered as a most effective and efficient public health intervention to reduce morbidity and mortality among children. Most of the children from developing countries are still not fully immunized due to multiple factors including lack of interventions, awareness, and financial constraints and due to limited resource. Conversely, this review has identified the effectiveness of interventions to increase the immunisation coverage among children of developing countries. Methods: Systematic review by using PRISMA statement (preferred reporting items for systematic reviews and meta-analyses) has been conducted in English published articles on Pub Med, Scopus, Cochrane, Medline and ISI by searching keywords like immunizations, childhood vaccination and developing countries has been accessed. Only randomised controlled trial and quasi-experimental studies designs were included in the final analysis based on quality assessment by adopting the Down and Black checklist and finally pooled analysis was done by random effect model. This systematic review has been approved and registered by University of York. Results: A total of 16,570 published articles were accessed and finally 10 fulfilled our criteria that were analysed and interpreted. It demonstrated that the interventions has shown significantly increase vaccine coverage for childhood cluster diseases (OR 2.136 and p <0.05).Furthermore, it has been proved that an effect was more prominent for DTP (OR 2.397 and p<0.05) and measles (OR 2.628 and p<0.05), not as much for polio (OR 2.284 and p>0.05) and full vaccination schedule (OR 1.342 and p>0.05). Conclusions: Systematic review has concluded that the professional interventions are an effective while in improving the child immunisation coverage for cluster diseases in developing countries, major effect on DTP and measles. Keywords: Professional interventions, immunizations, child vaccination, cluster diseases, developing countries and systematic review